2019
DOI: 10.1038/s41398-019-0373-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress dynamically regulates co-expression networks of glucocorticoid receptor-dependent MDD and SCZ risk genes

Abstract: Early-life adversity is an important risk factor for major depressive disorder (MDD) and schizophrenia (SCZ) that interacts with genetic factors to confer disease risk through mechanisms that are still insufficiently understood. One downstream effect of early-life adversity is the activation of glucocorticoid receptor (GR)-dependent gene networks that drive acute and long-term adaptive behavioral and cellular responses to stress. We have previously shown that genetic variants that moderate GR-induced gene tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Notably, clinical evidence shows that the vHPC, or the anterior hippocampal portion in humans, also modulates affective processes [8] associated with changes in brain volume, cell type [17], and gene expression [18]. Recently, we showed that stress induces greater alteration of gene expression change in the vHPC as opposed to the dorsal hippocampus [19] and others have characterized gene networks in the vHPC using disparate paradigms of stress [20][21][22]. However, genomic commonalities in the vHPC across multiple models of stress are largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, clinical evidence shows that the vHPC, or the anterior hippocampal portion in humans, also modulates affective processes [8] associated with changes in brain volume, cell type [17], and gene expression [18]. Recently, we showed that stress induces greater alteration of gene expression change in the vHPC as opposed to the dorsal hippocampus [19] and others have characterized gene networks in the vHPC using disparate paradigms of stress [20][21][22]. However, genomic commonalities in the vHPC across multiple models of stress are largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Many psychiatric disorders are multifactorial and influenced by both genetic predisposition and environmental factors [70][71][72][73]. Adverse early life events have been associated with an increased risk of mood and anxiety disorders [74]; for example, genetic variants associated with schizophrenia interact with early life stress to affect risk [75]. Moreover, childhood stress increases the risk for later psychiatric disorders [11]: temporary childhood neglect is associated with an increased incidence of ADHD [76], and child abuse associates with suicidal ideation and various psychiatric disorders [77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…The eQTL transcripts (etranscripts) regulated by these variants form tight co-expression networks. Using an animal model of exposure to adversity across development (Santarelli et al, 2017), we observed that different combinations of early and adult environments (supportive vs. stressful) substantially affect co-expression structure of these networks in a highly brain region-specific manner (Zimmermann et al, 2019). However, this set of eQTLs and regulated etranscripts was identified in a male only cohort.…”
Section: Introductionmentioning
confidence: 99%